Fungal endophyte communities in declining and vital oak (Quercus robur L.) trees - Matule, Baiba (SLU/Southern Swedish Forest Research Centre, 2018)
The role of microbiome in tree health is receiving increasing interest in forest pathology research. This study focuses on the abundance and diversity of fungal endophytes in pedunculate oak (Quercus robur L.) differentiating in vitality. Earlier studies with peri-urban, young oak trees have indicated that fungal endophyte diversity in woody tissues of oaks is lower in highly vital trees. In this thesis, the hypothesis that declining trees harbour a higher fungal diversity was tested in a production forest setting, using older trees. To test the hypothesis, endophytes were isolated from bark and xylem of Quercus robur L., using two types of agar-media to select for a broad range of fungi. Based on the morphological characters of the colonies the isolates grouped into 38 morphotypes and a group of singletons, and the frequency and diversity of fungi in different tissue types (bark and xylem of differently vital trees) was compared. The results indicate that endophyte communities of Quercus robur L. xylem and bark are more diverse in trees showing some symptoms of decline in comparison to the seemingly healthy-looking trees, but that the diversity was reduced in the most strongly declined trees. In addition, the results confirmed the earlier findings showing that bark associated endophyte communities are more diverse than xylem associated communities. I also found that samples of water agar harbored different assemblage of morphotypes comparing to malt extract agar. Future studies are required to characterize fungal endophyte communities in order to evaluate the interactions that take place within the complex, understudied networks and apply them in ecosystem management.